Heritage value attribution: The case of Sítio Alagadiço Novo – Fortaleza, Ceará - de Castro Teixera Maia, Marina; Lersch, Ines Martina (International Planning History Society Proceedings, 2018)
This work aims at retrieving the historical trajectory of Sítio Alagadiço Novo – Fortaleza, Ceará – birthplace of the romantic writer, José de Alencar. Having never before been considered under the yoke of a scientific investigation, Sítio Alagadiço is currently suffering from the lack of attention and use by the surrounding community. By assuming that the relation between cultural heritage and community is a matter of value attribution, it is essential to understand the paths which led to this conflicting situation. Therefore, we seek to retrieve the property’s history since the arrival of the Alencar family up to the time it was heritage-listed by the National Historic and Artistic Heritage Institute (IPHAN). Some of the questions raised throughout the process include: is the importance of the place due to the figure of José de Alencar and his literary heritage? What are the values assigned to it? Has the idea of upgrading the property as a historical asset come from the community? These questions guide the content of this paper. We intend to pursue the valuation process within its historical context and therefore reflect upon the inconsistency perceived between such valuation and the treatment currently given to the property.